Entrepreneurship in upper secondary level students - Hidalgo, José Felipe Ojeda; Arredondo-Hidalgo, María Guadalupe; León, José Luis Vital (Archives of Business Research, 2020)
Entrepreneurship is a relevant activity for the challenges of the current global economic crises, which have brought lack of employment opportunities. The present investigation was carried out through a sample of 2,005 upper-middle-level students from 14 campuses of the National College of Technical Professional Education, in the state of Guanajuato, Mexico. The objective was to achieve a typology of entrepreneurship in students at this level. The following variables were identified: Attraction to be an entrepreneur (AT), Initiative (IN), Knowledge of the activity (KN), Resistance to entrepreneur (RE), Dislike to undertake (DU), Social assessment (SA), Leadership (LE) and Determination and Courage (DC). The correlation analysis showed that there is a significant correspondence between the dimension of pleasure for entrepreneurship and the variables of: innovation, knowledge, resistance to entrepreneur and social valuation; likewise, the variable of dislike to undertake showed a negative correlation, and on the other hand, the innovation variable showed correlation with the variables: knowledge, resistance to entrepreneur and social valuation. Again, a negative correlation is observed with the variable of dislike to undertake. Finally, the knowledge variable showed a slight negative correlation with the variable of dislike to undertake.